Ground-nesting bees prefer bare ground areas on calcareous grasslands - Hanna Gardein; Yvonne Fabian; Catrin Westphal; Teja Tscharntke; Annika Hass (Global Ecology and Conservation, 2022)
Although most of the wild bee species are ground-nesting, little is known about their nesting requirements and the conservation measures to promote ground-nesting bees. Calcareous grasslands are one of the most species-rich habitats in Central Europe and therefore essential for protecting bee diversity. The management practices of calcareous grasslands are so far often focused on plant populations, but in order to support declining insect populations, additional measures have to be considered for nature conservation. As wild bees depend on the availability of nesting sites, we studied the effects of locally increased bare ground availability on ground-nesting bees on four large and four small calcareous grasslands in Central Germany. Vegetation cover of 24 experimental plots (1 m²) was removed. The number of bee nests as well as the presence of bees on these plots (here: nesting activity) were compared to 24 control plots during six sampling runs. Results showed that the number of bee nests on experimental plots was fourteen times higher compared to control plots, positively related to the surrounding flower cover and higher on steeper slopes, independent of grassland area. Moreover, the observed nesting activity on experimental plots was 2.5 times higher compared to the control and positively related to the currently prevailing soil surface temperature. Bee abundance quantified during transect walks increased on grasslands with a generally higher bare ground availability and a higher flower cover. In conclusion, our study emphasizes the need to consider the availability of nesting resources to promote the vast majority of wild bees, which are ground-nesting. They benefited from bare ground availability as well as adjacent floral resources, and experimental removal of the vegetation cover appeared to be a major, so far underestimated conservation practice.